Road pavement collapse from overloaded trucks due to traffic diversion: A case study of Minna-Kateregi-Bida Road, Nigeria. (January 2022) - Alhaji, Mustapha Mohammed; Alhassan, Musa; Adejumo, Taiye Waheed; Abdulkadir, Hamidu
Highlights: Road route survey was carried out along the entire stretch of the road to access the level of sudden collapse of the road. Development of geological map along the road route to ascertain the geological setup along the road. Conduction of trial pits within the worst sections of the road to study the soil profile below the subgrade layer and possible water level. All these investigations revealed organic soil layer and stiff clay soil layer as subgrade for the road structure with shallow water table. Abstract: Sudden failure of road pavement structure from Minna through Kataeregi to Bida in Niger State, Nigeria, occurred in 2020 due to high traffic volume of overloaded trucks. The high traffic volume was necessitated by the collapse of two alternative routes (Tegina-Makera-Mokwa and Lambata-Bida-Mokwa roads) that were previously being used by these heavy trucks. Methodology used to study the causes of this sudden failure includes interaction with the Niger State Ministry of works, visual route survey of the entire road, conduction of trial pits within the worst sections of the road and collection of soil samples for analysis and finally, generation of soil profile within these sections to show the probable causes of the sudden failure. Result of visual route survey revealed that the entire stretch of the road which geologically cut across basement complex from Minna to Kataeregi and Bida basin from Kataeregi to Bida, has failed with potholes, pavement cracks, ruts, large depressions and embankment failures. However, some sections were observed to have collapsed completely. Trial pits conducted within the collapsed sections also showed defects including thick organic soil layer underlying road embankment, clay of high plasticity underlying organic soil layer and shallow water table within the region of the basement complex. A long and high embankment across a wide river channel was observed to have failed due to the failure of the thin metal sheet tubes employed to move the heavy flood water across the embankment. It was then concluded that these defects resulted from poor geotechnical investigation prior to construction and the poor expertise of the firm involved in the construction of the road.